Educadores e Role-Playing Game (RPG): um estudo sobre design de experiências lúdicas on-line - Sá, Cristiane Freire de (2022)
This research aims to investigate, describe, and interpret the ludic experience lived by fourteen educators in the course named Laboratory of Culture and Ludic Language in Learning, designed from elements of the Role-Playing Game (RPG) and grounded on the Complex Educational Design (CED) developed by Freire (2013). To achieve this purpose, the theoretical supports provided by Salen's (2008), Salen and Zimmermann's (2012a, 2012b) conception of ludic experience, and Morin's (2015) ecology of action perspective were used. The works on educational experience written by Dewey (1929, 1953, 1959, 1971, 2008,2010) and by Varela, Thompson, and Rosch (2003), and about the ludic elements on human development theorized by Huizinga (2010), Benjamin (2009, 2018a, 2018b), Maturana (1998), and Maturana and Zoller (2004) were also relevant foundations in this study. This research has its textualization and thematization procedures grounded on the Complex HermeneuticPhenomenological Approach (CHPA), proposed by Freire (2010, 2012, 2017). The course on focus was developed in the extensionist context of the Distance Education Reference Center (CEAD) of the Federal Institute of São Paulo (IFSP), and the material generated throughout the interactions was interpreted according to the methodological framework selected. The outcomes of this study have the potential to contribute to educational design models guided by ludic elements to create educational ludic experiences, being able to be based on the educative RPG system developed by this research, named LórDe (Educational Design Lab)